Optimization of reaction parameters of cyclodextrin glycosyltransferase from bacillus licheniformis on cyclodextrin production - Rohaida, Che Man; Ravichandaran, Thiviashanti; Muhammad Taufiq, A. Rahman (2021)
Cyclodextrin is produced from enzymatic degradation of starch. Improves guest molecule’s chemical and physical properties. Optimization of the reaction parameter to maximize the production of CD